2012
DOI: 10.1007/s12272-012-0219-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-related effects of sodium arsenite on splenocyte proliferation and Th1/Th2 cytokine production

Abstract: Aging is associated with immune dysfunction and conditions such as inflamm-aging and immunosuppression. Arsenic, an environmental contaminant distributed worldwide, affects the immune system. This study tested the hypothesis that arsenic has distinct effects on T cell proliferation and the production of cytokines by activated T cells. Murine splenocytes from young (2 months) and aged (24-26 months) C57BL/6 mice were exposed to arsenite (As(3+)), the most toxic form of inorganic arsenic, and stimulated with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Mitogen induced T-cell proliferative response and cytokine secretion was also found to be suppressed in arsenic exposed population 15 , 19 and in-vitro arsenic exposed human PBMCs 14 , 16 , 17 . Similar response was observed in mouse model 20 22 .…”
Section: Introductionsupporting
confidence: 86%
“…Mitogen induced T-cell proliferative response and cytokine secretion was also found to be suppressed in arsenic exposed population 15 , 19 and in-vitro arsenic exposed human PBMCs 14 , 16 , 17 . Similar response was observed in mouse model 20 22 .…”
Section: Introductionsupporting
confidence: 86%
“…The authors found that at the highest doses of sodium arsenite, T lymphocytes underwent less mitogen-stimulated proliferation when pretreated (in the case of mitogens PHA and Con A) or simultaneously cultured (in the case of mitogen PHA only) with sodium arsenite, similar to results noted by Soto-Peña et al [14] and Kozul et al [60]. Another study by Cho et al [62] found that C57BL/6 splenocytes from young adult female mice exhibited reduced proliferation and IFN-γ production, as well as a non-significant decreasing trend in IL-2 production, when cultured with Con A, and increasing concentrations of sodium arsenite. The same downward trend in IL-2 production with increasing arsenic concentration was also noted for splenocytes cultured with anti-CD3 antibody, and the decrease was found to be significant at the highest dose of arsenic (2 μM).…”
Section: Arsenic Exposure and Immune Responsessupporting
confidence: 70%
“…A biphasic dose-dependent response was observed following As III or As V exposure of mitogen-stimulated human and bovine PBMC [119], demonstrating As immunosuppressive effects depend on the dose. As markedly suppressed lymphocyte secretion and/or mRNA levels of IFN-γ, IL-4 and IL-10 in different in vitro models [114,116,117]. As III also significantly impaired differentiation of human Th17 cells by repressing their expression and release of IL-17 and decreasing expression of RORγt, which regulates IL-17, through inactivation of JNK/c-Jun pathway [120].…”
Section: In Vitro Studiesmentioning
confidence: 99%